Child development five to eight [videorecording] - Sears, Twila; Laleman, Joseph P. (Meridian Education Corp., 1990)
Examines the development of a child during the ages from five to eight years old, including the changes that take place in a child as a result for starting school, the ways on which children in this age begin to set standards for themselves and the importance of self-stem and good self-image for young children. The importance of good role models and how role models affect a child's development are also discussed.